THE IMPACT OF ACCOUNTABILITY AND TRANSPARENCY ON FINANCIAL MANAGEMENT IN TOURISM VILLAGES: PARTICIPATION AS A MEDIATOR - Ni Made Rukmiyati; Ni Ketut Mareni; I Wayan Tuwi (JURNAL KEPARIWISATAAN, 2023)
Support from the community and village authorities is necessary for the development of a tourist village. The availability of funds to support the development of facilities and infrastructure is a crucial aspect in developing a tourist village. For this reason, the effectiveness of financial management in tourism villages is beneficial. Accountability, transparency, and community involvement are some of the characteristics that affect how well villages manage their finances. This research aims to investigate the direct and indirect effects of accountability and transparency on village financial management through community participation as a mediating variable. Stewardship theory, which portrays a circumstance where management is not driven by individual goals but is more focused on their major results in order to develop the organization, offers as the theoretical foundation for this research. In this study, the partial least squares (PLS) data analysis method with structural equation modeling (SEM) was utilized to test the hypothesis. Whereas to test the mediating variable, we will use the testing method of the Sobel test, namely testing the path coefficient of indirect influence. The seven hypotheses offered were significant, according to the findings of hypothesis testing using partial least squares (PLS). These findings demonstrate that involvement can moderate the connection between accountability and transparency in financial management. Following the study's findings, participation, accountability, and transparency all have an impact on how effectively finances are managed. So that these three things can be a concern for the village government, It is hoped that further research will enable the development and addition of other independent variables that will influence the effectiveness of financial management variables.